George Eliot's Daniel Deronda notebooks - Eliot, George 1819-1880 (Cambridge University Press, 1996)
George Eliot's notebooks from the years 1872–77 contain memoranda of her reading while she was preparing for and writing Daniel Deronda, together with the 'Oriental Memoranda' and other notes she recorded in the year following the novel's publication. Above all, the notebooks reveal her acquisition of a wide range of learning about Judaism and provide insight into the creative process of integrating that learning into Daniel Deronda. One of these notebooks is published in this 1996 book; others are offered in new transcriptions. They are all presented in a form which demonstrates the intellectual coherence underlying the diversity of the memoranda: translations are provided for the notes in German, French, Italian, Greek, and Hebrew; explanatory notes are offered, and interpretative links are made to the novel; primary sources are traced and the chronology of Eliot's reading outlined